Gut commensal bacteria-derived methionine is required for host reproduction by modulating RNA m6A methylation of the insulin receptor - Qiuyuan Zhang; ZhuRong Deng; Xiaoxue Li; Jiao Qiao; Ziniu Li; Peipei Liu; Alfred M. Handler; Bruno Lemaitre; Weiwei Zheng; Hongyu Zhang (Cell Reports, 2025)
Summary: Gut commensal bacteria promote host reproduction by modulating metabolism and nutrition, but the molecular mechanisms by which microbes regulate reproduction remain unclear. Here, we show that gut commensal bacteria promote host reproduction by providing the amino acid methionine, which controls the RNA m6A modification level of insulin receptor (InR) in the ovary of the invasive insect Bactrocera dorsalis. Antibiotic-treated B. dorsalis shows reduced RNA m6A methylation levels and methionine content, resulting in arrested ovarian development and decreased fecundity. The gut commensal bacterium Enterobacter hormaechei-derived metabolite methionine restores the decreased RNA m6A level and the reproductive defects. Notably, the knockdown of METTL3 and METTL14, two genes encoding the RNA m6A methyltransferases, reduces InR mRNA and protein levels and impairs ovarian development in B. dorsalis. Our findings further expand the functional landscape of RNA m6A modification to include nutrient-dependent control of ovarian development and highlight the essential role of epigenetic regulation in microbe-host interactions.